Mengoptimalkan Prakarsa Media Sosial untuk Mendukung Bisnis Make Up Artist di Ikatan Pengusaha Muslimah Indonesia (IPEMI) Kuranji Kota Padang - Nilam sari, Meci (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
This training activity on the use of social media for make-up artist businesses at IPEMI PC Kuranji is a form of community service. IPEMI PC Kuranji is a women's entrepreneur organization that makes it easier for its members to be creative and innovative in entrepreneurship. One of them is fighting for make-up artists at IPEMI PC Kuranji. There is so much competition everywhere that MUAs have to be smart in racking their brains so that their makeup service business can run smoothly. However, this increasingly fierce competition has made many novice MUAs confused about how to do it. One way to revive the MUA business is by managing and utilizing social media for their business.